The impact of physiological crowding on the diffusivity of membrane bound proteins. Issue 7 (11th January 2016) - Houser, Justin R.; Busch, David J.; Bell, David R.; Li, Brian; Ren, Pengyu; Stachowiak, Jeanne C.
Abstract : The diffusivities of membrane bound proteins follow a linearly decreasing trend with increasing membrane coverage, regardless of protein size. Abstract : Diffusion of transmembrane and peripheral membrane-bound proteins within the crowded cellular membrane environment is essential to diverse biological processes including cellular signaling, endocytosis, and motility. Nonetheless we presently lack a detailed understanding of the influence of physiological levels of crowding on membrane protein diffusion. Utilizing quantitative in vitro measurements, here we demonstrate that the diffusivities of membrane bound proteins follow a single linearly decreasing trend with increasing membrane coverage by proteins. This trend holds for homogenous protein populations across a range of protein sizes and for heterogeneous mixtures of proteins of different sizes, such that protein diffusivity is controlled by the total coverage of the surrounding membrane. These results demonstrate that steric exclusion within the crowded membrane environment can fundamentally limit the diffusive rate of proteins, regardless of their size. In cells this "speed limit" could be modulated by changes in local membrane coverage, providing a mechanism for tuning the rate of molecular interaction and assembly.